Fixation and Immunolabeling of Brain Slices: SNAPSHOT Method. Issue 1 (1st April 2015) - Dissing‐Olesen, Lasse; MacVicar, Brian A.
Abstract: Acute brain slices are widely used in neuroscience because this preparation enables pharmacological interventions in a timely manner, similar to what is currently done in cultured cell studies, while preserving the natural cytoarchitecture. However, compared with cells in culture and thin cryostat sections, acute brain slices are not commonly used for immunolabeling because of poor fixation and antibody penetration. Thus, we have established a novel protocol to overcome these issues. We named this protocol SNAPSHOT (StaiNing of dynAmic ProcesseS in HOt‐fixed Tissue) because it describes a simple approach for preserving the morphology of fine dynamic cellular processes at the exact time of fixation and for improving the penetration of antibodies. We have previously shown that SNAPSHOT preserves the ultrastructure of the tissue and allows for a uniform immunolabeling throughout a 300 μm thick slice. SNAPSHOT has recently proven to be beneficial in addressing several unique biological questions. © 2015 by John Wiley & Sons, Inc.